The kids calculator : what's your footprint? / Romiza Md Nor and Haleeda Azwa Abdul Hadi - Romiza, Md Nor; Haleeda Azwa, Abdul Hadi (Universiti Teknologi MARA, Perak, 2016)
There are various ways to reduce the amount of CO2 emission. This paper investigates the effectiveness of using a medium which is an interactive web based carbon footprint calculator for kids called oped to allow children to calculate their carbon footprint based on their daily activities that contribute to the emission of carbon dioxide (CO2) for educational purposes. CFCkids also provides information about climate change and tips to reduce carbon footprint. Evaluation on usability and content had been conducted with children aged ten to twelve years old. From the findings, it has been discovered that CFCkids can increase the knowledge of children about climate change and how they can naturalize the environment from the result of their carbon footprint calculation.